MODERN TECHNOLOGIES FOR OPTIMIZING THE PROCESS OF EDUCATIONAL PROGRAM DEVELOPMENT (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The study examines contemporary approaches to the use of digital technologies in the development of educational programs for preschool institutions. Both international and national experiences in implementing information and communication solutions that ensure flexibility, adaptability, and individualization of the educational process are analyzed. Particular attention is given to the impact of digitalization on the quality of program design and implementation, the role of educators in a digital environment, and the conditions necessary for effective transformation of the educational system. Based on the analysis, recommendations are proposed to improve the content and methods of preschool education in line with modern technological trends.